Studies and analysis on interlayer bonding in asphalt pavements - Jaskuła, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper describes research works of interlayer bonding of asphalt layers conducted at Gdansk University of Technology. The studies included laboratory and field tests, and calculation of pavement structures with different interlayer bonding models. Laboratory tests included interlayer bonding tests using the direct shear method which evaluated the influence of selected factors on interlayer bonding: the type and the amount of the emulsion, the method and the effectiveness of compaction, vulnerability to dirt, water and repeated shear loads. Field works were focused on the impact of interlayer bonding of asphalt layers on the deflection of pavement structure and the back-calculated stiffness modulus of asphalt mixtures. The analyses of the field tests also included the impact of the asphalt layers compaction ratio on interlayer bonding. Computational analyses of asphalt pavement structures consisted of the simulation of different interlayer bonding in a multi-layered elastic half-space. Calculations were also made by using the finite element method within cohesion and friction models to simulate interlayer bonding.